Mechanosensitive molecular mechanisms of myocardial fibrosis in living myocardial slices. (6th February 2022) - Nunez‐Toldra, Raquel; Kirwin, Thomas; Ferraro, Elisa; Pitoulis, Fotios G.; Nicastro, Laura; Bardi, Ifigeneia; Kit‐Anan, Worrapong; Gorelik, Julia; Simon, Andre R.; Terracciano, Cesare M.
Abstract: Aims: Altered mechanical load in response to injury is a main driver of myocardial interstitial fibrosis. No current in vitro model can precisely modulate mechanical load in a multicellular environment while maintaining physiological behaviour. Living myocardial slices (LMS) are a 300 μm‐thick cardiac preparation with preserved physiological structure and function. Here we apply varying degrees of mechanical preload to rat and human LMS to evaluate early cellular, molecular, and functionality changes related to myocardial fibrosis. Methods and results: Left ventricular LMS were obtained from Sprague Dawley rat hearts and human cardiac samples from healthy and failing (dilated cardiomyopathy) hearts. LMS were mounted on custom stretchers and two degrees of diastolic load were applied: physiological sarcomere length (SL) (SL = 2.2 μm) and overload (SL = 2.4 μm). LMS were maintained for 48 h under electrical stimulation in circulating, oxygenated media at 37°C. In overloaded conditions, LMS displayed an increase in nucleus translocation of Yes‐associated protein (YAP) and an up‐regulation of mechanotransduction markers without loss in cell viability. Expression of fibrotic and inflammatory markers, as well as Collagen I deposition were also observed. Functionally, overloaded LMS displayed lower contractility (7.48 ± 3.07 mN mm −2 at 2.2 SL vs. 3.53 ± 1.80 mN mm −2 at 2.4 SL). The addition of the profibrotic protein interleukin‐11 (IL‐11) showed similar results to the application of overload with enhanced fibrosis (8% more of collagen surface coverage) and reduced LMS contractility at physiological load. Conversely, treatment with the Transforming growth factor β receptor (TGF‐βR) blocker SB‐431542, showed down‐regulation of genes associated with mechanical stress, prevention of fibrotic response and improvement in cardiac function despite overload (from 2.40 ± 0.8 mN mm −2 to 4.60 ± 1.08 mN mm −2 ). Conclusions: The LMS have a consistent fibrotic remodelling response to pathological load, which can be modulated by a TGF‐βR blocker. The LMS platform allows the study of mechanosensitive molecular mechanisms of myocardial fibrosis and can lead to the development of novel therapeutic strategies.